Comparison between the electrical conductivity method and radicle emergence test as a rapid test of sorghum seed vigor - Nugraheni, Nugraheni; Pujiasmanto, Bambang; Samanhudi, Samanhudi; Sakya, Amalia Tetrani (Universitas Padjadjaran, 2023)
Sorghum (Sorghum bicolor L. Moench) belongs to multipurpose crops. All parts of sorghum can be used both as main products and derivative products; some derivative products produced from the sorghum plant consist of sugar, bioethanol, biomass, handicraft raw materials and starch. This study aims to determine the time required for testing the vigor and viability of sorghum seeds using the electrical conductivity and radicle emergence methods. The study was conducted in two experimental stages using a completely randomized design. The first experiment consisted of two factors: the number of sorghum seeds (40, 70 and 100 grains) and the volume of soaking water (75, 100, 125, and 150 ml). The second experiment consisted of two factors: research method (germination/control method, electrical conduction method, and radicle emergence method) and varieties (consisted of Numbu, Kawali, Suri 3, and Suri 4). The first experiment's results showed that the best electrical conductivity method on Suri 4 varieties were 40 seeds and 150 ml water volume. The electrical conductivity value is negatively correlated with Germination capacity, vigor index, growth of speed, maximum growth potential, and sprout growth rate. Time needed for Electrical Conductivity method in this study was three days. The germination period of 96 hours gives the best results on the radicle emergence of sorghum seed varieties. Vigor index, growth of speed, germination capacity, and maximum growth potential are positively correlated with the value of radicula emergence.Keywords: Electrical Conductivity, Radicle emergence, Vigor, Viability, Germination